2021
DOI: 10.3390/ani11071849
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Streptococcus uberis Associated with Clinical Mastitis in Dairy Cows: Virulence Traits, Antimicrobial and Biocide Resistance, and Epidemiological Typing

Abstract: Mastitis remains a serious problem for dairy animals. The misappropriation of antimicrobial agents helps accelerate resistance, which poses a serious challenge in controlling environmental S. uberis infection. Here, we study the virulence attributes, antimicrobial and biocide resistance, and epidemiological typing of S. uberis recovered from bovine clinical mastitis in dairy farms of diverse hygienic interventions in Egypt. The overall S. uberis infection rate was 20.59%; all were multidrug-resistant (MDR). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…These studies show that EmrE homologs in other bacterial species can confer resistance to similar substrates, but the scope of the assays was limited to common multidrug resistance substrates and detection of resistance phenotypes. Here we analyze SMRs from three bacterial species of interest for the potential to cause disease in humans or animals for comparison with EmrE: Staphylococcus aureus (SAsmr) (42)(43)(44)(45), Pseudomonas aeruginosa (PAsmr) (46,47), and Francisella tularensis (FTsmr) (48). These particular transporters were selected on the basis of disease relevance, sequence diversity (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These studies show that EmrE homologs in other bacterial species can confer resistance to similar substrates, but the scope of the assays was limited to common multidrug resistance substrates and detection of resistance phenotypes. Here we analyze SMRs from three bacterial species of interest for the potential to cause disease in humans or animals for comparison with EmrE: Staphylococcus aureus (SAsmr) (42)(43)(44)(45), Pseudomonas aeruginosa (PAsmr) (46,47), and Francisella tularensis (FTsmr) (48). These particular transporters were selected on the basis of disease relevance, sequence diversity (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Mastitis is one of the most prevalent diseases in dairy cows, producing well-recognized detrimental effects on animal health and profitability of dairy farms ( Ruegg, 2017 ; Abd El-Aziz et al, 2021a ). Treatment of mastitis is often applied without prior knowledge of cause-related agents and mostly with broad-spectrum antimicrobials, which are known to enhance resistance evolution to a greater extent.…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, the occurrence of virulence genes was similar [ 10 ], whereas in others, the situation was quite different. As an example of the different detection rates, the oppF gene was detected in almost 100% of isolates in Thailand, New York State, and the Czech Republic [ 3 , 30 ], but in the study of El-Aziz et al [ 31 ] in Argentina, the oppF gene was detected in only 12% of the S. uberis isolates. The results of this study also showed a very different occurrence of the pauA/skc gene.…”
Section: Discussionmentioning
confidence: 99%